2021
DOI: 10.1088/1361-648x/abf381
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, optical, and thermoelectric properties of Janus In-based monochalcogenides

Abstract: Inspired by the successfully experimental synthesis of Janus structures recently, we systematically study the electronic, optical, and electronic transport properties of Janus monolayers In2XY (X/Y = S, Se, Te with X № Y) in the presence of a biaxial strain and electric field using density functional theory. Monolayers In2XY are dynamically and thermally stable at room temperature. At equilibrium, both In2STe and In2SeTe are direct semiconductors while In2SSe exhibits an indirect semiconducting behavior. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 68 publications
2
38
0
Order By: Relevance
“…In the past decades, reducing the dimensionality of the TE material as a practical approach to improving the TE performance was studied. [8][9][10] Generally, layered structures have ultralow lattice thermal conductivities since the interface interactions between the neighboring layers lead to a large phonon anharmonicity. Therefore, layered structures were predicted as promising TE materials.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, reducing the dimensionality of the TE material as a practical approach to improving the TE performance was studied. [8][9][10] Generally, layered structures have ultralow lattice thermal conductivities since the interface interactions between the neighboring layers lead to a large phonon anharmonicity. Therefore, layered structures were predicted as promising TE materials.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Beside the Janus structures of TMDs, Janus monochalcogenides have also been of great interest in recent years. 26,27 Guo and co-worked demonstrated that the Janus group III monochalcogenides have much higher piezoelectric coefficients than that of the corresponding group-III monochalcogenide monolayers. 28 These Janus structures have also been proven to have efficient photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Many subsequent studies have focused on the 2D Janus structures and the heterostructures formed from these new materials. [15][16][17][18][19][20] With their vertical broken mirror symmetry structure, they have had many extraordinary physical properties with potential applications in the fields of materials science, energy conversion, and spintronics. [21][22][23] Recently, a new 2D structure MoSi 2 N 4 has been successfully fabricated by chemical vapor deposition.…”
Section: Introductionmentioning
confidence: 99%